Задача приведения для регулярной системы полых круговых цилиндров с произвольной решеткой периодов - Толмачев, С.Т.; Юхимович, Д.Л. (Технічна електродинаміка, 2011)
On basis of multifield method for an arbitrary doubly periodic gratings the explicit formulas for tensor of reduced doubly periodic system penetrability of hollow circular cylinders with arbitrary magnetic penetrabilities of areas have been obtained.